Клинико-лабораторная оценка эффективности кариес-профилактических мероприятий у детей г. Ужгород при использовании различных источников водоснабжения = Clinical and laboratory evaluation of caries preventive measures in children in Uzhhorod by using different sources of water supply - Zombor, E. V.; Denga, E. M. (Journal of Education, Health and Sport, 2016)
Zombor E. V., Denga E. M. Клинико-лабораторная оценка эффективности кариес-профилактических мероприятий у детей г. Ужгород при использовании различных источников водоснабжения = Clinical and laboratory evaluation of caries preventive measures in children in Uzhhorod by using different sources of water supply. Journal of Education, Health and Sport. 2016;6(7):59-66. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.57112 http://ojs.ukw.edu.pl/index.php/johs/article/view/3657 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 25.05.2016. Revised 25.06.2016. Accepted: 28.06.2016. УДК 616.314-039.71 КЛИНИКО-ЛАБОРАТОРНАЯ ОЦЕНКА ЭФФЕКТИВНОСТИ КАРИЕС-ПРОФИЛАКТИЧЕСКИХ МЕРОПРИЯТИЙ У ДЕТЕЙ г. УЖГОРОД ПРИ ИСПОЛЬЗОВАНИИ РАЗЛИЧНЫХ ИСТОЧНИКОВ ВОДОСНАБЖЕНИЯ Е. В. Зомбор, О. В. Деньга Государственное учреждение «Институт стоматологии Национальной академии медицинских наук Украины» Реферат Приведены результаты исследований, свидетельствующие о высокой кариес-профилактической эффективности разработанных и патогенетически обоснованных для детей г. Ужгород, использующих воду из разных источников водоснабжения с разным минеральным составом, дифференцированных комплексов профилактики основных стоматологических заболеваний, применение которых позволило получить кариес-профилактический эффект 41-49 %, улучшить показатели тканей пародонта, уровня гигиены полости рта и биохимические показатели ротовой жидкости. Ключевые слова: дети, источники водоснабжения, комплексная профилактика, стоматологический статус. CLINICAL AND LABORATORY EVALUATION OF CARIES PREVENTIVE MEASURES IN CHILDREN IN UZHHOROD BY USING DIFFERENT SOURCES OF WATER SUPPLY E. V. Zombor, E. M. Denga State Institution "Institute of Stomatology National Academy of Medical Sciences of Ukraine" Summary Introduction. Various macro and microelementoses in drinking water leads to disruption in the child’s body metabolism, cell metabolism, enzyme activity, and dental status, require the development of effective and comprehensive prevention interventions. The objective. Assessment of prevention effectiveness of dental caries in children 6-7 years of Uzhgorod, using water from sources with different mineral composition. Materials and methods. In-depth study was involved 96 children of 6-7 years of Uzhgorod, using different sources of water. Children of basic groups received 2 times a year, preventive and treatment complexes, considering low levels of fluoride in drinking water, general hardness, nitrate and strontium content. Results. Conclusions. High efficiency of developed for children Uzhgorod differentiated complexes prevention of major dental diseases, using water from different water sources with different mineral composition, the use of which allowed us to obtain caries-preventive effect of 41-49%, improve performance fabrics periodontal, oral hygiene and biochemical indices of oral liquid. Key words: children, dental caries, micro- and macroelementoses drinking water, genetic predisposition.